The effect of additional Silk worm (Tubifex sp.) on artificial feed on the number of larva Guppy fish (Poecilia reticulata) - Ashari Kautsar; Muhammad Marzuki; Andre Rachmat Scrabra (Universitas Muhammadiyah Malang, 2022)
Aquaculture does not only cover consumption fish production, there is also ornamental fish production. Guppy fish (Poecilia reticulata) is one of the popular ornamental fish because of its many varieties and easy maintenance and cultivation.The aim of the study was to evaluate the effect of giving silk worms (Tubifex sp.) on spawning parent guppy (Poecillia reticulata) and to analyze the appropriate dose of silk worms on spawning brood guppy (Poecillia reticulate). This study used an experimental method with the addition of tropical almond leaf powder. The experimental design used was a completely randomized design (CRD) consisting of 5 treatments, namely treatment P0 (100% artificial feed/control), P1 (95% artificial feed, 5% silk worms.), P2 (90% artificial feed, silk worms). 10%), P3 (85% artificial feed, 15% silk worms), P4 (80% artificial feed, 20% silk worms) and each treatment was repeated 3 times. The results showed that the addition of silk worms (Tubifex sp.) in artificial feedsignificant effect on the parameters of absolute weight growth of broodstock, feed conversion ratio, gonadosomatic index, and the number of larvae produced. Meanwhile, the survival rate parameters for both broodstock and guppy larvae had no significant effect.The highest average value of each parameter occurred in the P4 treatment.